IMPROVING WORK QUALITY THROUGH EXPLANATION OF COMMUNITY WORK CULTURE VALUES IN HUMBAHAS FOOD ESTATE : PENINGKATAN KUALITAS KERJA MELALUI PENYULUHAN NILAI-NILAI BUDAYA KERJA MASYARAKAT DI FOOD ESTATE HUMBAHAS - Mhd. Pujiono; Nelvita; Murniati Br. Barus (Universitas Lancang Kuning, 2022)
This service aims to implement the values ​​of the local community’s work culture in developing better management of the Humbang Hasundutan (Humbahas) food estate. This activity is one of the implementations of the cooperation between the Humlingual local government and the University Sumatera Utara, which is carried out in the form of counselling and socialization by providing materials. The target audience for this activity is the community around the food estate in Dolok Sanggul District, Humbang Hasundutan Regency, North Sumatra. In this case, the target community is the teachers and students of SMP Negeri 4 Dolok Sanggul. The activity method used is the lecture and discussion method. This socialization & counselling was attended by 30 people who manage the Humbahas food estate area. After attending this activity, the participants can understand the importance of knowledge of the cultural values ​​of the Batak marsiadapari and marsiurupan in improving the quality of work to create high productivity without compromising the harmony between the environment and fellow human beings.